2016
DOI: 10.17759/sps.2016070305
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of group, micro-group and interpersonal identities of employees in production groups

Abstract: The article represents the results of mathematical and statistical analysis of the links between the levels of the identity of employees (group, micro-group and interpersonal) by three components (cognitive, affective and behavioral) in 37 industrial groups with expertise in different fields. The significant linear relationship between micro-group and interpersonal identity (for all components), high linear relationship between group identity and micro-group identity (only for affective component) and the lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Conversely, the identification of workers with structural units may be the basis for their interpersonal ID. These data are consistent with the studies that found associations among some social ID foci [ 15 , 34 , 54 ] and between some social IDs and interpersonal IDs [ 37 , 63 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Conversely, the identification of workers with structural units may be the basis for their interpersonal ID. These data are consistent with the studies that found associations among some social ID foci [ 15 , 34 , 54 ] and between some social IDs and interpersonal IDs [ 37 , 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…A significant positive linear relationship has been found between organizational ID and group ID [ 15 , 34 , 50 ], between organizational ID and sub-organizational ID [ 54 ], between micro-group ID and ID with peers [ 37 ], and between organizational ID and ID with the supervisor [ 35 , 36 , 63 ]. In particular, it was shown that the identification of employees who tend to follow the lead of the leader plays a decisive role in the subsequent formation of collective identifications—organizational and group IDs [ 35 ].…”
Section: Relative Strength Of Foci and Dimensions Of Employee Identif...mentioning
confidence: 99%
See 1 more Smart Citation
“…All the identifications-interpersonal, micro-group, and group-comprise cognitive, affective, and behavioral components. An earlier study of working groups shows that (a) micro-group identification is significantly stronger in all components in comparison with interpersonal and group ones (Sidorenkov et al, 2014); (b) there is a significant linear correlation between interpersonal identification and micro-group identification in all components, non-linear correlation is registered between micro-group and group identifications, whereas there is not any correlations between interpersonal and group identifications (Sidorenkov & Dorofeev, 2016); (c) micro-group identification in all components is significantly positively related with some indicators of group performance, whereas interpersonal and group identifications are not significantly related with them (Sidorenkov et al, 2014). These findings implicitly indicate that different identifications and their components can relate with behaviors (including OCB) and group characteristics in different ways.…”
Section: Relations Of Identification Dimensions With Contribution To Group Activitiesmentioning
confidence: 96%